(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Allocation of costs to prevent and environmental improvement conditions is an incurred cost by the company that arises from the negative impact of the company’s operations. The environmental costs incurred are expected to have a direct impact on environmental performance and financial performance. This research wants to see how much effect environmental costs and environmental performance have on the financial performance of mining companies listed on the Indonesia Stock Exchange (BEI). The population in this study came from 24 mining sector companies using purposive sampling techniques and for the five year observation period 2018 - 2022, 40 company data samples were obtained. Samples of data used come from annual reports, financial reports published on the Indonesian Stock Exchange and Sustainability Reports. To carry out data analysis and obtain regression results in this research, a statistical tool, namely Eviews 9, was used. The research results show that environmental costs have an effect on environmental performance, environmental performance has no effect on financial performance and simultaneously environmental costs and performance have an effect on financial performance.